Opportunities and Challenges to Increase the Engagement of Young Citizens in Promoting Peace in Society - Mawarti, Rista (Jurnal Pendidikan Kewarganegaraan Undiksha, 2025)
Student interest in gaining contextual learning experiences about peace is increasing. Therefore, the development of a service-learning model combined with peace education and increasing citizen engagement is the main focus of this study. The method used is a qualitative approach with a participatory design involving lecturers and students in the Social Praxis course at the Law and Citizenship Department, Faculty of Social Sciences, Universitas Negeri Malang. The results of the study show that: 1) the implementation of the learning model has the opportunity to increase the knowledge, skills, and engagement of young citizens in promoting peace through material deepening activities, preparation of activity plans, to the implementation of peace education programs; 2) the challenges of implementing the learning model is the development of a imaginary paradigm about peace with the category of social media users so that students need to get a more intense in-depth study of the material; 3) the evaluation of the implementation of the learning model is an improvement in the intensity of the supervision of student activity designs by lecturers to improve the quality of programs run by students.